(untitled) (Kairaranga, 2008)
There may be an implicit assumption amongst some New Zealand educators that minority cultures should assimilate wholly into the New Zealand way of life, shedding aspects of their own culture that conflict with the mainstream. Some others assert that encouraging minority students to maintain their culture, including language and traditions, results in positive academic and social achievement. This paper challenges some of the possible covert assumptions that may be prevalent amongst educators; assumptions that prevent these children from transitioning smoothly into our schools. It outlines the importance of valuing cultural differences, promoting a sense of personal identity and encouraging the use of first languages.